Post traumatic cerebral oedema in severe head injury is related to intracranial pressure and cerebral perfusion pressure but not to cerebral compliance - UdinNujaimin, Nujaimin; Awang, Mohamed Saufi; Rahman, Ghani; Idris , Badrisyah; Sayuti , Sani; Idris , Zamzuri; Mohamed , Kamarul; Abdullah , Jafri (Elsevier, 2009)

(untitled)
This was a prospective cohort study, carried out in the Neuro Intensive Care Unit, Department of Neurosciences, Hospital Universiti Sains Malaysia, Kubang Kerian Kelantan. The study was approved by the local ethics committee and was conducted between November 2005 and September 2007 with a total of 30 patients included in the study. In our study, univariate analysis showed a statistically significant relationship between mean intracranial pressure (ICP) as well as cerebral perfusion pressure (CPP) with both states of basal cistern and the degree of diffuse injury and oedema based on the Marshall classification system. The ICP was higher while CPP and compliance were lower whenever the basal cisterns were effaced in cases of cerebral oedema with Marshall III and IV. In comparison, the study revealed lower ICP, higher mean CPP and better mean cerebral compliance if the basal cisterns were opened or the post operative CT brain scan showed Marshall I and II. These findings suggested the surgical evacuation of clots to reduce the mass volume and restoration of brain anatomy may reduce vascular engorgement and cerebral oedema, therefore preventing intracranial hypertension, and improving cerebral perfusion pressure and cerebral compliance. Nevertheless the study did not find any significant relationship between midline shifts and mean ICP, CPP or cerebral compliance even though lower ICP, higher CPP and compliance were frequently observed when the midline shift was less than 0.5 cm. As the majority of our patients had multiple and diffuse brain injuries, the absence of midline shift did not necessarily mean lower ICP as the pathology was bilateral and even when after excluding the multiple lesions, the result remained insignificant. We assumed that the CT brain scan obtained after evacuation of the mass lesion to assess the state basal cistern and classify the diffuse oedema may prognosticate the intracranial pressure and cerebral perfusion pressure thus assisting in the acute post operative management of severely head injured patients. Hence post operative CT brain scans may be done to verify the ICP and CPP readings postoperatively. Subsequently, withdrawal of sedation for neurological assessment after surgery could be done if the CT brain scan showed an opened basal cistern and Marshall I and II coupled with ICP of less than 20 mmHg. [Asian J Surg 2009;32(3):157–62]